Developmental toxicity and estrogenic activity of antimicrobial phenolic-branched fatty acids using in silico simulations and in vivo and in vitro bioassay - Zhang, Xinwen; Ngo, Helen; Wagner, Karen; Fan, Xuetong; Wu, Changqing (Frontiers in Toxicology, 2024)
Due to the growing safety and environmental concerns associated with biocides, phenolic-soy branched chain fatty acids (phenolic-soy BCFAs) are synthesized as new bio-based antimicrobial agents. Safety evaluation is essential before the wide adoption of these new antimicrobial products. This study was initiated to evaluate the safety of four phenolic-soy BCFAs (with phenol, thymol, carvacrol, or creosote branches). Methyl-branched iso-oleic acid, phenol, and creosote were included in the study as controls. In silico toxicity simulation tools predicted that the phenolic BCFAs had much higher toxicities to aquatic organisms than free phenolics did, while the opposite was predicted for rats. The developmental toxicity of four phenolic-soy BCFAs was assessed using an in vivo chicken embryonic assay. Results showed that creosote-soy BCFA had much lower mortality rates than creosote at the same dosages. Additionally, creosote-soy BCFA and methyl-branched iso-oleic acid induced minimal estrogenic activity in the concentration range of 10 nM - 1 µM. Carvacrol-soy BCFA treatments significantly increased (p < 0.05) oxidative stress levels with higher thiobarbituric acid reactive substances in the livers of chicken embryos. Altogether, the phenolic-soy BCFAs, especially creosote-soy BCFA, reported in this study are potentially promising and safer bio-based antimicrobial products.